A Case Study on the Selection of Materials for Eye Lenses. (4th April 2011) - Findik, Fehim
Abstract : A case study on the selection of materials for eye lenses is reported by means of Ashby's materials selection diagrams. In this study, 6 polymer materials of PMMA, PC, PS, PVC, PET, and PA are reviewed and their properties are found from the selection diagrams of Ashby and compared in a table. The final results confirmed that PMMA (acrylic) is the best material for eye lenses. The outcome also showed that the present material is environmental friendly being nontoxic and recyclable.